Parents' Weekend. Photo 015 - Leonard, Spencer (Tufts Archival Research Center, 2008)
Parents' Weekend. Catherine Clinton, author of 'Harriet Tubman: The Road to Freedom,' kicks off the Tisch Library's installation of the national touring exhibition 'Forever Free: Abraham Lincoln's Journey to Emancipation.' A question-and-answer session and book signing follows.Tisch Library, Hirsh Reading Room, 3:30-5 p.m.